Building medical physics continuing education programming tailored to the site-specific needs in low- and middle-income countries: an initial framework - Swanson, William; Kovalchuk, Nataliya; Uwadiae, Iyobosa; Goss, Matt; Brovchuk, Serhii; Zelinskyi, Ruslan; Ainsworth, Victoria; Parker, Stephanie; Avery, Stephen; Ngwa, Wil; Kisling, Kelly (Frontiers in Medicine, 2025)
Low- and middle-income countries (LMICs) are significantly underserved in cancer management resources, contributing the majority of annual cancer incidence and mortality globally. Many patients in LMICs have limited accessibility to radiotherapy, which serves as a standard cancer treatment for many patients, due to lacking infrastructure to support the patient population and trained professionals to deliver treatment. Recent efforts have been made to supplement foundational medical physics knowledge in LMICs by providing continuing education opportunities to establish strong educational leaders at the local level. While high-income countries have ample resources to support well-established education and training standards, it is important to adapt the curricula in a resource-responsible manner. This education and training should be relevant and appropriate to the clinical setting in LMICs. This article collates the experience of members of the American Association of Physicists in Medicine and international collaborators to develop and administer optimized medical physics education with limited resources. The framework presented here is intended to be used as a preliminary guide to developing education and training programs specific to the needs of medical physicists in LMICs.